2016
DOI: 10.1371/journal.pone.0166345
|View full text |Cite
|
Sign up to set email alerts
|

Area-Level and Individual-Level Factors for Teenage Motherhood: A Multilevel Analysis in Japan

Abstract: BackgroundTeenage motherhood is strongly associated with a range of disadvantages for both the mother and the child. No epidemiological studies have examined related factors for teenage motherhood at both area and individual levels among Japanese women. Therefore, we performed a multilevel analysis of nationwide data in Japan to explore the association of area- and individual-level factors with teenage motherhood.MethodsThe study population comprised 21,177 mothers living in 47 prefectures who had their first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
3
10
0
1
Order By: Relevance
“…This finding is supported by studies done in Ethiopia, 17 Nigeria, 19 Philippines, 22 and Japan. 23 This may be due to educated adolescents have better knowledge and skills to prevent pregnancy. However, the primary level and uneducated adolescents have limited access to sexual and reproductive health information and services needed to prevent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by studies done in Ethiopia, 17 Nigeria, 19 Philippines, 22 and Japan. 23 This may be due to educated adolescents have better knowledge and skills to prevent pregnancy. However, the primary level and uneducated adolescents have limited access to sexual and reproductive health information and services needed to prevent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…15 Babies of teenagers face higher risks of low birth weight, preterm delivery, and severe neonatal conditions. 10 As evidenced by different studies there are factors associated with teenage pregnancy which include; age, [16][17][18][19] marital status, [17][18][19][20][21] educational status, 17,22,23 employment, 17,19,24 residence, 16,17,25 occupation, 17,26 wealth status, 13,26,27 culture, 19,28 peer pressure, 13,29 family history of teenage pregnancies, 18,30 early marriage, 31 forced marriage, 27 rape, 32 community contraceptive use, 24 and community wealth status. 22,-23,-33 Since reducing the high rate of teenage pregnancy and maternal mortality is one the key Sustainable Development Goals (SDG), target 3.1 and 3.7, it has been addressed by the Ethiopian government and other key development partners.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified many predictive factors of teenage pregnancy. Some of them include age (Alemayehu, Haider, & Habte, 2010;Ayanaw Habitu, Yalew, & Azale Bisetegn, 2018;Ayele, Gebregzabher, Hailu, & Assefa, 2018;Nwosu, 2017), economic status (Amoran, 2012;Gyan, 2013), educational status (Alemayehu et al, 2010;Baba, Iso, & Fujiwara, 2016;Habito, Vaughan, & Morgan, 2019), religion (Alemayehu et al, 2010;Ayele et al, 2018;Beyene et al, 2015;Gideon, 2013;Nwosu, 2017), culture (Mchunu, Peltzer, Tutshana, & Seutlwadi, 2012;Nwosu, 2017), place of residence (Alemayehu et al, 2010;Ayanaw Habitu et al, 2018;Birhanu, Kebede, Kahsay, & Belachew, 2019), family history of teenage pregnancies (Ayele et al, 2018;Wall-Wieler, Roos, & Nickel, 2016), rape (Tiruneh, 2010), peer's and partners' behaviours (Gyan, 2013;Vincent & Alemu, 2016), contraceptive use (Ezegwui, Ikeako, & Ogbuefi, 2012), forced marriage (UNFPA (United Nations Population Fund), 2013), early marriage (Presler-Marshall & Jones, 2012), family and community attitudes (Baba et al, 2016;Habito et al, 2019;Odimegwu & Mkwananzi, 2016), and the use of mass media (Alemayehu et al, 2010;Ezegwui et al, 2012;Nwosu, 2017) are contributing factors to the increase of unintended pregnancy among adolescents.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Adolescent pregnancy is a known contributing factor to the global maternal mortality rate owing to the high incidence of unsafe abortion practices among these age groups [2,4]. Adolescent motherhood is a vital concern in maternal and child health [5]. The dearth of care among adolescent mothers has advanced to a surged peril of poor maternal and neonatal health sequelae [6].…”
Section: Introductionmentioning
confidence: 99%
“…This predisposes adolescent mothers to a greater risk of eclampsia, prolonged labour, puerperal endometritis, STIs and systemic infections [2,4,7,8]. Consequently, the infants of adolescent mothers face greater risks of low birth weight, preterm delivery and severe neonatal conditions [2,4,5,7,8]. Evidence exists that children born to adolescent mothers are likely to become adolescent mothers in the future [5].…”
Section: Introductionmentioning
confidence: 99%